Determination of Total Flavonoid Content of Raru Bark Extract: Cotylelobium Melanoxylon Pierre at Various Methanol Concentrations and Antibacterial Activity Against Staphylococcus - Hazizah, Mautia; Ridwanto, Ridwanto; Daulay, Ani Sartika (Newinera Publisher, 2025)
Raru bark (Cotylelobium melanoxylon (Hook.f) Pierre) is a plant with antidiabetic properties. Raru bark plants contain flavonoids, saponins, and tannins. The purpose of this study was to determine the class of secondary metabolites contained in the sample, determine flavonoid levels, and determine antibacterial activity against Staphylococcus aureus bacteria. This research includes processing samples made simplisia, then extracted and thickened using rotary evaporatory. Simplisia was tested for phytochemical screening to determine the content of metabolite compounds, in addition to testing its characteristics. The next test was the determination of total flavonoid content using UV-Vis spectrophotometry. Followed by testing antibacterial activity against Staphylococcus aureus. The results of phytochemical screening obtained flavonoids, tannins, and saponins. Flavonoid levels were 42.4308 ± 2.4739 mgQE/g; 38.1813 ± 1.5799mgQE/g; and 23.8153 ± 3.049276 mgQE/g, respectively. In testing antibacterial activity using concentrations of 10%, 40%, 70%, and 100%, and the highest concentration is found at a concentration of 100% which is 19.83mm.